Cognitive enhancement kept within contexts: neuroethics and informed public policy - Shook, John R.; Galvagni, Lucia; Giordano, James (Frontiers in Systems Neuroscience, 2014)
Neurothics has far greater responsibilities than merely noting potential human enhancements arriving from novel brain-centered biotechnologies and tracking their implications for ethics and civic life. Neuroethics must utilize the best cognitive and neuroscientific knowledge to shape incisive discussions about what could possibly count as enhancement in the first place, and what should count as genuinely “cognitive” enhancement. Where cognitive processing and the mental life is concerned, the lived context of psychological performance is paramount. Starting with an enhancement to the mental abilities of an individual, only performances on real-world exercises can determine what has actually been cognitively improved. And what can concretely counts as some specific sort of cognitive improvement is largely determined by the classificatory frameworks of cultures, not brain scans or laboratory experiments. Additionally, where the public must ultimately evaluate and judge the worthiness of individual performance enhancements, we mustn’t presume that public approval towards enhancers will somehow automatically arrive without due regard to civic ideals such as the common good or social justice. In the absence of any nuanced appreciation for the control which performance contexts and public contexts exert over what “cognitive” enhancements could actually be, enthusiastic promoters of cognitive enhancement can all too easily depict safe and effective brain modifications as surely good for us and for society. These enthusiasts are not unaware of oft-heard observations about serious hurdles for reliable enhancement from neurophysiological modifications. Yet those observations are far more common than penetrating investigations into the implications to those hurdles for a sound public understanding of cognitive enhancement, and a wise policy review over cognitive enhancement. We offer some crucial recommendations for undertaking such investigations, so that cognitive enhancers that truly deserve public approval can be better identified.